Prevalence of intimate partner violence and abuse and associated factors among women enrolled into a cluster randomised trial in northwestern Tanzania. (December 2017) - Kapiga, Saidi; Harvey, Sheila; Muhammad, Abdul; Stöckl, Heidi; Mshana, Gerry; Hashim, Ramadhan; Hansen, Christian; Lees, Shelley; Watts, Charlotte
Abstract Background Intimate partner violence (IPV) is recognised as an important public health and social problem, with far reaching consequences for women's physical and emotional health and social well-being. Furthermore, controlling behaviour by a partner has a similar impact on women's well-being, yet little is known about the prevalence of this type of behaviour and other related abuses in Tanzania and in other sub-Saharan African countries. Methods We conducted a cross-sectional study to determine the lifetime and past 12-month prevalence of physical and sexual IPV, economic abuse, emotional abuse and controlling behaviour among ever-partnered women in Mwanza, Tanzania. Women (N = 1049) were enrolled in an ongoing trial (Maisha study) to assess the impact of microfinance combined with gender training on participants' experience IPV, and other related outcomes. Interviews were conducted by same sex interviewers to collect information about socio-demographic characteristics, experiences of specific acts of IPV and abuse, and symptoms of poor mental health status. Results Overall, about 61% of women reported ever experiencing physical and/or sexual IPV (95% CI: 58–64%) and 27% (95% CI: 24–29%) experienced it in the past 12 months. Partner controlling behaviour was the most prevalent type of abuse with 82% experiencing it in their lifetime and 63% during the past 12 months. Other types of abuses were also common, with 34% of women reporting economic abuse and 39% reporting emotional abuse during the past 12 months. The prevalence of IPV and abuses varied by socio-demographic characteristics, showing much higher prevalence rates among younger women, women with young partners and less educated women. After we adjusted for age and socio-economic status, physical violence (OR = 1.8; 95% CI: 1.3–2.7) and sexual violence (OR = 2.8; 95% CI: 1.9–4.1) were associated with increased reporting of symptoms of poor mental health. Similarly, experience of abuse during the past 12 months was associated with increased reporting of symptoms of poor mental health. Conclusions The high prevalence of IPV and abuses and its strong links with symptoms of poor mental health underline the urgent need for developing and testing appropriate interventions in settings like Tanzania to tackle both violence and abusive behaviours among intimate partners. Trial registration ClinicalTrials.gov – IDNCT02592252, registered retrospectively on 13 August 2015.